Lexicon of Cultural Values in The Salama Loko Tradition: An Anthropolinguistic Study - Sri Wahyu Lestari; Abdul Muhid; Agus Syahid; Hilda Hastuti; Syamsurrijal Syamsurrijal (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
Salama Loko is traditional ceremony of the Bima and Dompu people (Mbojo tribe) when the pregnancy reaches seven months. This ceremony has its own process that contains symbolic meaning. This study aim to find out and analysis the lexicons and cultural values during Salama Loko processing ceremony in Risa Village, Woha Sub-district, Bima Regency. The method used in this study is qualitative descriptive analysis. The data collection used in this study through observation, interviews, and documentation. The result show that the lexicons used in Salama Loko ceremony are mantra, tembe kanefe, bunch of bananas, white rise, coconut & coconut oil, dolu (egg) and bongi monca (yellow rice), candle, wura piti (throwing coins), mangonco (salad). The moral values of Salama Loko tradition are to express the happiness and joy to Almighty God and depict self-purification to pray to Almighty God.